Intrinsic brain abnormalities in chronic rhinosinusitis associated with mood and cognitive function - Lin, Simin; Nie, Miaomiao; Wang, Bingshan; Duan, Shaoyin; Huang, Qianwen; Wu, Naiming; Chen, Zhishang; Zhao, Hengyu; Han, Yi (Frontiers in Neuroscience, 2023)
Background: Chronic rhinosinusitis (CRS) poses a risk for the development of emotional and cognitive disorders. However, the neural evidence for this association is largely unclear. Resting-state functional magnetic resonance imaging (rs-fMRI) analysis can demonstrate abnormal brain activity and connectivity and contribute to explaining the potential pathophysiology of CRS-related mood and cognitive alterations. Methods: Chronic rhinosinusitis patients (CRS, n = 26) and gender- and age-matched healthy control subjects (HCs, n = 38) underwent resting-state functional MRI scanning. The amplitude of low-frequency fluctuations (ALFF) was calculated to observe the intrinsic brain activity. The brain region with altered ALFF was further selected as the seed for functional connectivity (FC) analysis. Correlation analysis was performed between the ALFF/FC and clinical parameters in CRS patients. Results: Compared with HCs, CRS patients exhibited significantly increased ALFF in the left orbital superior frontal cortex and reduced connectivity in the right precuneus using orbital superior frontal cortex as the seed region. The magnitude of the orbital superior frontal cortex increased with inflammation severity. In addition, ALFF values in the orbital superior frontal cortex were positively correlated with the hospital anxiety and depression scale (HADS) scores. The ROC curves of altered brain regions indicated great accuracy in distinguishing between CRS patients and HCs. Conclusions: In this study, patients with CRS showed increased neural activity in the orbital superior frontal cortex, a critical region in emotional regulation, and this region also indicated hypoconnectivity to the precuneus with a central role in modulating cognition. This study provided preliminary insights into the potential neural mechanism related to mood and cognitive dysfunctions in CRS patients.